2002
DOI: 10.1037/h0088856
|View full text |Cite
|
Sign up to set email alerts
|

Short-term group play therapy with Chinese earthquake victims: Effects on anxiety, depression and adjustment.

Abstract: This study investigated the effectiveness of short-term child-centered group play therapy in elementary school settings with Chinese children in Taiwan who experienced an earthquake in 1999. Children in the experimental group scored significantly lower on anxiety level and suicide risk after play therapy than did children in the control group. The effects of the treatment support previous studies of play therapy with American children. These findings reveal the possibility of disaster intervention services ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 22 publications
4
78
0
Order By: Relevance
“…Ray (2011), Ray et al (2008) and Shen (2002) demonstrated the effectiveness of brief and short-term CCPT, such as twice weekly within two to three months. Jones and Landreth (2002) demonstrated the effectiveness of 12 sessions within three weeks.…”
Section: Cbcl Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ray (2011), Ray et al (2008) and Shen (2002) demonstrated the effectiveness of brief and short-term CCPT, such as twice weekly within two to three months. Jones and Landreth (2002) demonstrated the effectiveness of 12 sessions within three weeks.…”
Section: Cbcl Resultsmentioning
confidence: 99%
“…This section will The results of this study are consistent with other intensive play therapy studies that demonstrated improved effectiveness when increasing the number of counseling sessions in the same or less amount of time. Ray (2011), Ray et al (2008) and Shen (2002) demonstrated the effectiveness of brief and short-term CCPT, such as twice weekly within two to three months. Jones and Landreth (2002) demonstrated the effectiveness of 12 sessions within three weeks.…”
Section: Effectiveness Of Intensive Ccpt With Children With Externalimentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, more play therapists are needed to meet the needs of child clients (Porter, Hernandez-Reif, & Jessee, 2009). Moreover, many researchers have addressed the effectiveness of Child-Centered Play Therapy (CCPT) training in helping play therapists improve their attitude, knowledge, and skills (Homeyer & Rae, 1999;Hunt, 2006;Kagan & Landreth, 2009;Kao & Chang, 2007;Kao & Landreth, 1997;Lindo et al, 2012;Shen, 2002;Shen & Herr, 2003). Their findings have shown positive impacts on the counseling profession and children with difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study found that 81 percent of participants agreed that play specialists are needed in helping children in hospital wards. Shen (2002) studied in a group format at a rural elementary school in Taiwan. The relationship between the children and the counselor helped to decrease the level of anxiety because of the sense of safety, security, permissiveness, and acceptance by the counselor, all based on the child-centered approach.…”
Section: Introductionmentioning
confidence: 99%